you can solve it in a much simpler manner. 1. First note that 2x^2-19x +39 = (2x^2 - 21x +49) + 2(x-5) 2. Then you can substitute t= (2x^2 - 21x +49)/(x-5) 3. Rewriting the equation, you obtain: t^2 + (t+2)^2 = 10 => (t^2-1) + (t+2)^2 - 3^2 = 0 => 2(t-1)(t+3) = 0 => t= 1 or t=-3. 4. Then, solve for x, when t=-3 => 2x^2-18x+34=0=> x = (9+/-sqrt(13))/2 when t=1 => x^2-11x+27=0 => x = (11+/-sqrt(13))/2
@Sandaruwan_06234 күн бұрын
මොන්ටි සෝරි යන මටත් තේරුනා
@SathsaraKusumsiri-xg9tr4 күн бұрын
❤❤❤
@KavinduKeshara-he1iz4 күн бұрын
Sir , ජ්යාමිතිය විභාග ගණන් ටිකට ඇරලා දාන්නකෝ
@lasithasineth10854 күн бұрын
sir mama dan 11 wasare. mama thigonometry video okkoma baluwa sirge. mata dan me lesson eka simple. thank you sir.